The Role and Optimization Strategies of MIS in Improving the Quality of University Library Management - Nurul Hamidah (Library and Information Science Study Program, Faculty of Humanities, Univ. Diponegoro, 2026)
Background: Despite the growing emphasis on digital transformation in higher education, many university libraries in Indonesia still rely on manual and fragmented management systems. This gap hinders the development of data-driven planning and evaluation, resulting in service inefficiencies and poorly aligned decision-making. Previous studies have focused mainly on digital collection development and service theory, with limited attention to the strategic integration of Management Information Systems (MIS) for continuous quality improvement. Moreover, empirical research examining how MIS supports library performance and user-centered innovation in real institutional settings remains scarce. This study addresses that gap by exploring MIS implementation as a foundation for evidence-based library management.Objective: This study aims to analyze the role of the Management Information System (MIS) in supporting planning and evaluation processes in library management. It also seeks to identify practical and effective strategies to improve service quality through data-driven MIS optimization in higher education libraries.Methods: Using a qualitative method with a case study approach, the research was conducted over a three-month period. Data focused on MIS functions and strategic implementation, collected from the head librarian, library staff, system administrators, and users (students and lecturers) through in-depth interviews, observation, and documentation. Data validity was ensured through triangulation and member checks, and analysis followed Miles and Huberman’s interactive model.Results: Findings show that MIS enhances planning accuracy, automates reporting, and provides real-time access to user data, enabling better performance evaluation and decision-making. Strategies such as staff training, data- based standard operating procedures (SOPs), digital service transformation, and analytical dashboards contributed to improved responsiveness and accountability in library services.Conclusion: The study concludes that MIS plays a strategic role in transforming library management into a more adaptive, efficient, and data-driven system. When effectively implemented, MIS strengthens institutional decision- making, aligns services with user needs, and establishes a culture of continuous quality improvement in university libraries.